ACTUAL TICK-BORNE INFECTIONS IN CRIMEA - M. V. Gorovenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
The Crimean Peninsula is located in the Northern part of the Black sea, from the East it is washed by the Sea of Azov, to the South and West by the Black Sea. The unique geographical and climatic conditions facilitate leptospirosis, tularemia, tick-borne encephalitis, Lyme disease, intestinal yersiniosis, pseudotuberculosis, hemorrhagic fever with renal syndrome, Crimean-Congo hemorrhagic fever, Mediterranean fever, Q-fever and other infectious diseases natural foci formation on the territory of Crimea Republic. Tick-borne natural focal infections have the most significance due to favorable epidemiologic conditions especially on the background of high raid ticks attacks on people. A leading role in the epizootology and epidemiology of tick-borne natural-focal infections of the Crimea are playing Ixodidae that occur in different landscape-climatic zones, with the greatest their species diversity is observed in mountain-foothill, forest and forest-steppe regions. There are about 30 species in Ixodidae fauna of the Crimean Peninsula. Ticks species composition identification shows that over 50% of people attacks episodes in the Crimea on recent years is caused by Ixodes ricinus ticks species, the remaining are associated with Haemophisalis punctata, Rhipicephalus sanguineus, Hyalomma marginatum, Dermacentor marginatus and other. Refusal of treatment in medical institutions of the people affected by tick bites, and the possibility of an attack on people subtle phases of mites are lubricates the real picture of the frequency of contacts of the population with ticks and complicates the forecasting of the epidemiological situation. This review summarizes the available information about spreading of tick-borne encephalitis, Lyme disease, Mediterranean and Crimean-Congo haemorrhagic fevers on the territory of Crimea Republic and demonstrates the modern trends and manifestations of epidemic process of these nosological forms. The results obtained in the analysis of our investigations and literature data, showed that the conditions of globalization lead to an increase in the frequency of contacts of the population with natural foci, and one of the most common tick-borne natural focal infections on the territory of the Peninsula are Lyme disease and the Mediterranean fever. Epidemiological analysis of the prevalence of tick-borne encephalitis and Crimean-Congo haemorrhagic fever in Crimea revealed a decrease in the activity of natural foci of these infections at the present stage. The problem of tick-borne natural focal infections in Crimea Republic requires further careful study.